Assessment of exercise-induced changes in von Willebrand factor as a marker of severity of aortic stenosis. Issue 1 (4th March 2020) - Zelis, Jo M; Zimmermann, Frederik M; Andriessen, Froukje P J; Houthuizen, Patrick; Van de Ven, Jop; Leuverman, Jolanda; Johnson, Nils P; Pijls, Nico H J; Scharnhorst, Volkher; Van 't Veer, Marcel; Tonino, Pim A L
Abstract : Background: Loss of high-molecular-weight multimers (HMWMs) of von Willebrand factor (vWF) occurs due to high shear stress in patients with aortic stenosis. As symptoms of aortic stenosis occur during exercise, measurement of vWF during exercise might identify patients with aortic stenosis of clinical importance. The aim of this pilot study is to evaluate whether vWF changes over time as a result of exercise in patients with asymptomatic moderate or severe aortic stenosis. Methods: Ten subjects were analysed for changes in vWF by measuring HMWMs and closure time with adenosine diphosphate (CT-ADP). All subjects underwent a full stress test on a bicycle ergometer. At rest and at peak exercise, a transthoracic echocardiogram was performed. HMWMs and CT-ADP were assessed at baseline, during and after exercise. Results: HMWMs and CT-ADP did not change significantly during exercise, p=0.45 and p=0.65, respectively. HMWMs and CT-ADP correlated well, Spearman's rho −0.621, p<0.001. HMWMs during peak exercise did not correlate with maximal velocity measured, p=0.21. CT-ADP during exercise correlated well with the maximal echocardiographic velocity over the aortic valve (AV), rho 0.82, p=0.04. Conclusions: In a cohort of 10 patients with moderate or severe aortic stenosis, we observed no significant change in vWF biomarkers during exercise. Peak CT-ADP during exercise showed a good correlation with peak AV velocity measured with echo. Although CT-ADP is an easy test to perform and could be an alternative for peak AV velocity measured during exercise, our results suggest that it can only detect large changes in shear stress.